A novel method for calculating the energy cost of turning during running - Hatamoto Y; Yamada Y; Fujii T; Higaki Y; Kiyonaga A; Tanaka H (Dove Medical Press, 2013)
Yoichi Hatamoto,1 Yosuke Yamada,2 Tatsuya Fujii,3 Yasuki Higaki,3 Akira Kiyonaga,3 Hiroaki Tanaka31Graduate School of Sports and Health Science, Fukuoka University, Nanakuma Jonan-ku Fukuoka, Japan; 2The Fukuoka University Institute for Physical Activity, Nanakuma Jonan-ku Fukuoka, Japan; 3Faculty of Sports and Health Science, Fukuoka University, Nanakuma Jonan-ku Fukuoka, JapanAbstract: Although changes of direction are one of the essential locomotor patterns in ball sports, the physiological demand of turning during running has not been previously investigated. We proposed a novel approach by which to evaluate the physiological demand of turning. The purposes of this study were to establish a method of measuring the energy expenditure (EE) of a 180° turn during running and to investigate the effect of two different running speeds on the EE of a 180° turn. Eleven young, male participants performed measurement sessions at two different running speeds (4.3 and 5.4 km/hour). Each measurement session consisted of five trials, and each trial had a different frequency of turns. At both running speeds, as the turn frequency increased the gross oxygen consumption (V · O2) also increased linearly (4.3 km/hour, r = 0.973; 5.4 km/hour, r = 0.996). The V · O2 of a turn at 5.4 km/hour (0.55 [SD 0.09] mL/kg) was higher than at 4.3 km/hour (0.34 [SD 0.13] mL/kg) (P < 0.001). We conclude that the gross V · O2 of running at a fixed speed with turns is proportional to turn frequency and that the EE of a turn is different at different running speeds. The Different Frequency Accumulation Method is a useful tool for assessing the physiological demands of complex locomotor activity.Keywords: energy expenditure, turning, turn frequency, running speed, V · O2, heart rate